The Role of Organizational Leaders in Creating Internal Tolerance of Religious Communities in Karakan Village, Weru District, Sukoharjo Regency - Widoyo, Agus Fatuh; Mujiyati, Mujiyati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Harmony between people in general, both of the same religion and outside the religion, can be realized if each other can respect and appreciate each other. Every religion teaches about peace and harmony in life, reality shows that religious pluralism can trigger its adherents to clash with each other and conflict occurs. Religious conflicts do not only occur between different religions or what is known as inter-religious, but conflicts often occur between people in one religion. The purpose of this study was to determine the role of organizational leaders in creating internal tolerance among religious people in Karakan Village, Weru District, Sukoharjo Regency. This study uses a qualitative descriptive approach, by collecting data through observation, interviews and documentation. This study uses the theory of persuasive communication strategies. Research Results The role of Islamic organizational leaders in Karakan Village as agents of change in promoting tolerance cannot be underestimated. Through example, dialogue, and collaboration, they have succeeded in overcoming various obstacles, including differences in theological views and minimal formal communication.